Analisis Efisiensi Teknis Dan Inefisiensi Teknis Usahatani Padi Sawah Kecamatan Tanah Sepenggal Kabupaten Bungo: Penelitian - Eli Yefta Gultom; Saidin Ninggolan; Rozaina Ningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The objectives of this study are, To describe the picture of paddy farming in Tanah Sepenggal District, Bungo Regency, to analyze the factors that influence actual and frontier production and measure the technical efficiency of paddy farming in Tanah Sepenggal District, Bungo Regency, and to analyze socio-economic factors on the technical inefficiency of paddy farming in Tanah Sepenggal District, Bungo Regency. To determine actual production, frontier, technical efficiency using the stochastic frontier method and to determine technical inefficiency using the stochastic frontier inefficient method. The results of the study indicate that the use of production inputs such as land area, seeds, fertilizers have a significant effect on output in an overall manner. In the frontier production function, the production factors of land area, seeds, fertilizers and herbicides are factors that increase variation. The production factor with a negative value that is able to reduce production risk is labor significantly on frontier production, while the one that increases production insignificantly is Herbicide.